Stem cells from basic research to therapy (CRC Press, Taylor & Francis Group, 2014)
Preface: the first volume of Stem cells deals with the fundamental principles that govern embryonic and somatic stem cell biology. Historically, the identification and characterization of such pathways and general rules of stemness occurred during embryonic development and volume I reflects this with topics spanning from cell cycle regulation, epigenetics, and asymmetric cell division in a number of organ systems from planarian to human.